2020
DOI: 10.4049/jimmunol.1901059
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Drivers of Lymphocyte Organization in Vertebrate Mucosal Surfaces: Revisiting the TNF Superfamily Hypothesis

Abstract: The adaptive immune system of all jawed vertebrates relies on the presence of B and T cell lymphocytes that aggregate in specific body sites to form primary and secondary lymphoid structures. Secondary lymphoid organs include organized MALT (O-MALT) such as the tonsils and Peyer patches. O-MALT became progressively organized during vertebrate evolution, and the TNF superfamily of genes has been identified as essential for the formation and maintenance of O-MALT and other secondary and tertiary lymphoid structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…The organization of the mucosal immune system in mammals is thought to support efficient antigen trapping and rapid activation of the adaptive immune response ( 82 ). Organized-MALT (O-MALT) in mammals include Peyer’s patches in the gut and tonsils in the naso-pharyngeal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The organization of the mucosal immune system in mammals is thought to support efficient antigen trapping and rapid activation of the adaptive immune response ( 82 ). Organized-MALT (O-MALT) in mammals include Peyer’s patches in the gut and tonsils in the naso-pharyngeal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also reported the existence of a MALT associated with the mouth and the pharynx ( 32 , 33 ). In mammals, the organization of MALTs is well defined into regions where disorganized immune cells are scattered, hence forming a diffuse mucosal immune system, and into organized lymphoid aggregates such as Peyer’s patches in the gut and Waldeyer’s ring of tonsils in the nasopharyngeal area ( 34 ). In contrast, the fish mucosal immune system has long been perceived as a set of scattered immune cells spread along mucosal territories ( 19 , 27 ).…”
Section: Introductionmentioning
confidence: 99%